1. Select positive integers a and b such that a^3-(a-1)^3=(b^2)+(b-1)^2 starting with {a,b}={1,1}, numbering successive solutions {a
1,b
1}...{a
n,b
n}
2. Select positive integers x and y such that 3x^2-2y^2=1 starting with {x,y}={1,1}, again numbering successive solutions {x1,y1}...{xn,yn}
3. Let n exceed 1. Let {xn-1, yn-1}={X,Y}; let {an, bn}={A,B}.
Prove that X+Y=2(B-A).
Part 2:
The integer solutions, (xn, yn), of 3x2 - 2y2 = 1 (1), are given by
(sqrt(3) + sqrt(2))2n-1 = xn sqrt(3) + yn sqrt(2) for n = 1, 2..
Thus: xn = (p2n-1 + q2n-1)/(2*sqrt(3)) and yn = (p2n-1 - q2n-1)/(2*sqrt(2))
where p = sqrt(3) + sqrt(2), q = sqrt(3) - sqrt(2) and pq = 1.
This gives values of (x, y) as (1, 1), (9, 11), (89, 109), (881, 1079),...
with recurrence relations: xn = 10xn-1 - xn-2 and yn = 10yn-1 - yn-2
Part 1:
The equation a3 - (a - 1)3 = b2 + (b - 1)2 can be rearranged to give
3(2a - 1)2 - 2(2b - 1)2 = 1, which is (1) with a = (x + 1)/2 and b = (y + 1)/2.
Therefore the solutions for (a, b) are (1, 1), (5, 6), (45, 55), (441, 540),..
Part 3:
2(B - A) = 2(bn - an) = yn - xn
= (p2n-1 - q2n-1)/(2*sqrt(2)) - (p2n-1 + q2n-1)/(2*sqrt(3))
= [p2n-1(sqrt(3) - sqrt(2)) - q2n-1(sqrt(3) + sqrt(2)]/(2sqrt(6))
=(p2n-1q - q2n-1p)/(2sqrt(6))
= (p2n-2 - q2n-2)/(2sqrt(6)) since pq = 1
Also X + Y = xn-1 + yn-1
= (p2n-3 + q2n-3)/(2sqrt(3)) + (p2n-3 - q2n-3)/(2sqrt(2))
= [p2n-3(sqrt(3) + sqrt(2)) - q2n-3(sqrt(3) - sqrt(2))]/(2sqrt(6))
= (p2n-3p - q2n-3q)/(2sqrt(6))
= (p2n-2 - q2n-2)/(2sqrt(6))
Therefore: 2(B - A) = X + Y
Edited on May 27, 2011, 9:33 pm
|
Posted by Harry
on 2011-05-27 21:32:24 |